2017
DOI: 10.1016/j.rser.2017.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Review and classification of barriers and enablers of demand response in the smart grid

Abstract: Demand for flexibility in electricity systems and the transition to the Smart Grid is increasing opportunities for demand response (DR). However, there are many barriers which prevent the full potential of DR being realised. Unlocking of this potential, through identification of DR enablers, can be aided through systematic classification and analysis of DR barriers. To this end, while previous works mostly focused on individual aspects, this paper develops a comprehensive 'socio-techno-economic' review, classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
174
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(176 citation statements)
references
References 76 publications
0
174
0
2
Order By: Relevance
“…It has been also reported that there was not enough international collaboration regarding SG technology standards [21,23]. It is noteworthy that not international, but local efforts have been made though, as stated by an exponential increase in venture capital funding for SG start-ups in the U.S. [22].…”
Section: Current Status Of Grid Modernizationmentioning
confidence: 99%
“…It has been also reported that there was not enough international collaboration regarding SG technology standards [21,23]. It is noteworthy that not international, but local efforts have been made though, as stated by an exponential increase in venture capital funding for SG start-ups in the U.S. [22].…”
Section: Current Status Of Grid Modernizationmentioning
confidence: 99%
“…Part of the consumption can be shifted, but for substantial shifts, it requires a relative high reward or price benefit for the consumer, making the current business cases for the residential market difficult to realize . Moreover, a suite of economic, social, technical, political, and regulatory barriers to demand response still needs to be overcome . For the large deployment of renewables into the electricity system, we need to maximize the potential of direct consumption of the renewable‐generated energy as a complementary approach to demand response.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, a suite of economic, social, technical, political, and regulatory barriers to demand response still needs to be overcome. 13 For the large deployment of renewables into the electricity system, we need to maximize the potential of direct consumption of the renewable-generated energy as a complementary approach to demand response. This requires rethinking how energy storage can support direct consumption in the most cost-effective ways.When wind-and solar-generated energy is fed directly into the electricity grid, then cost is already competitive with existing electricity generation based on fossil fuels.…”
mentioning
confidence: 99%
“…Efficiently integrating distributed RE generation systems [3][4][5] is a key research topic because the most used renewable energies-photovoltaic (PV) solar energy [6,7], wind energy [8,9] and marine energy [10]-are intermittent and more difficult to store [11] and integrate without affecting the quality of the electrical network [12] or the electricity prices [13]. The current proliferation of small-scale urban PV in buildings [14] and urban wind generators [15] can help home electricity consumers become also producers ("prosumers") [16] using the smart grid (SG) [17,18] and micro-grids (µ−Gs) [19] concepts.…”
Section: Introductionmentioning
confidence: 99%